Negara dan Alquran di Indonesia: Studi Kasus Tafsir Tematik Kementerian Agama Islam - Wildan Imaduddin Muhammad (Qur'an and Hadith Academic Society, 2018)
This article discusses scientific interpretation of the Quran by ministry, done by of religious the researcher. This qualitative study discusses how the interpreters selected by the ministry interpret verses about the creation of human. This article finds that they interpret the verses of the Quran, using scientific sources and logic to explain them which are related to sains.